A Discussion over IFRS' Adoption in Islamic Countries - Stefana Maria Dima; Bogdan Dima; Ovidiu Megan; Luminiþa Paiusan (Journal of Accounting and Management Information Systems (JAMIS), 2014)
The main objective of this paper is to test a research hypothesis regarding the preference for IFRSs adoption in Islamic countries. The hypothesis has been tested on a dataset of 38 Islamic countries inside the framework of a Discrete and Limited Dependent Variable Model. We have obtained robust evidences of a negative association between IFRSs adoption and the weight of Muslim population. In order to evaluate the robustness of the results we considered as control variable the Index of Economic Freedom. The control variable appears to have a statistically significant positive impact on IFRSs adoption, so full adoption of IFRSs is more likely to occur for countries with a higher degree of economic freedom.
Keywords: M41; 650; Islam; accounting; IFRSs; AAOIFI